The Duke [videorecording (DVD)] - Bean, Richard, 1956-; Coleman, Clive, 1961-; Broadbent, Jim; Mirren, Helen; Whitehead, Fionn, 1997-; Maxwell Martin, Anna, 1977-; Goode, Matthew, 1978-; Bandeira, Jack; Kelly, Aimee, 1993-; Spencer, Charlotte (Sony Pictures Home Entertainment, 2022)
Set in 1961 when Kempton Bunton, a 60-year-old taxi driver, stole Goya's portrait of the Duke of Wellington from the National Gallery in London. It was the first (and remains the only) theft in the Gallery's history. Kempton sent ransom notes saying that he would return the painting on condition that the government agreed to provide television for free to the elderly. What happened next became the stuff of legend. Only 50 years later did the full story emerge a startling revelation of how a good man set out to change the world and in so doing saved his son and his marriage to Dorothy Bunton.